Polymorphisms of genes controlling homocysteine levels and IQ score following the treatment for childhood ALL. (April 2005) - Krajinovic, Maja; Robaey, Philippe; Chiasson, Sonia; Lemieux-Blanchard, Emilie; Rouillard, Méélanie; Primeau, Melanie; Bournissen, Facundo Garcia; Moghrabi, Albert
Introduction: One of the causes of long-term morbidity associated with the treatment of acute lymphoblastic leukemia (ALL) is late neurotoxicity manifesting as impairment of higher cognitive functions. Cranial radiation therapy (CRT) and chemotherapeutic agents, particularly methotrexate (MTX), are often suggested to be major contributing factors for its development. Homocysteinemia that arises as a result of MTX-induced folate depletion was proposed to play a role in MTX-related neurotoxicity. Several enzymes are essential to maintain the homocysteine levels. Their different functional forms, associated with common genetic polymorphisms, may modulate homocysteine levels and thereby influence MTX-associated neurotoxicity.Objectives: To test this hypothesis we assessed whether the variants of the methylene tetrahydrofolate reductase (MTHFR), methionine synthase (MTR), methionine synthase reductase (MTRR), cystathionine ββ-synthase (CBS) and endothelial nitric acid synthase (eNOS, NOS3) genes, acting either independently or in conjunction with other risk factors, influenced the cognitive functioning in ALL patients. The influence of the genes was measured by estimating the change in IQ scores over a period of 4 years post ALL diagnosis.Results: Two variants, the CBS 844ins68 polymorphism and NOS3894 T homozygosity, were associated with a change in IQ scores (p = 0.01 and 0.007, respectively). A multivariate model obtained through step-wise selection pointed to the importance of the NOS3894 TT genotype only. This effect appears to be dependent on CRT; IQ decline was apparent among individuals with the894TT genotype who received radiation therapy (p = 0.03). Furthermore, additional factors affecting IQ were identified, including the treatment administered (i.e., CRT; p = 0.02) and a younger age at diagnosis (p = 0.003), and the modifying effect of the treatment protocols was also noted (p = 0.04).Conclusion: The results suggest that NOS3 genotyping might identify individuals that are susceptible to intellectual impairment following ALL treatment.